Financial Data Security and SIEM: Protecting Sensitive Financial Information in Banking and Fintech Systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Financial Technology (Fintech) companies thrive on data security and trust. Customers willingly entrust these organizations with their valuable personal and financial information. Failure to preserve this trust could erode the very foundation they rely on to conduct their business. Robust cybersecurity measures and solutions have become a necessity in an era where many fintech organizations are increasingly embracing digital transformation. SIEM solutions use multiple data security monitoring tools and effortlessly fit in the fintech environment. This paper reviews the importance of SIEM systems in fintech space.